#### Answer

$8-3(x+6)=-10-3x$

#### Work Step by Step

"Eight decreased by...."
$8-...$
"...three times the sum of a number and six"
$... 3(x+6)$
Expression:
$8-3(x+6)$
Simplified,
$8-3(x+6)=8-3x-18=-10-3x$

Published by
Pearson

ISBN 10:
0321867327

ISBN 13:
978-0-32186-732-2

$8-3(x+6)=-10-3x$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.